Sustainable design of pervious concrete using waste glass and recycled concrete aggregate. (10th October 2019) - Lu, Jian-Xin; Yan, Xin; He, Pingping; Poon, Chi Sun
Abstract: This study designed an eco-friendly pervious concrete (PC) product using waste glass cullet (WGC) and recycled concrete aggregate (RCA) by dry-mixed compaction technique. The mechanical properties, water permeability behavior and related pore structure characteristics, thermal conductivity of the PCs were determined. The experimental results showed that the use of silica fume in the cement paste was effective to compensate for the low compressive strength of the PCs due to the use of narrowed graded aggregates without the incorporation of fine particles (less than 2.36 mm). Although the incorporation of recycled aggregates (i.e. WGC and RCA) into the PCs led to reductions in compressive strength, the water permeability of the PCs was improved, especially for the PCs prepared with WGC, as the use of WGC was conducive to improving the water permeability due to the negligible water absorption nature and smooth surface of glass cullet. Another encouraging result indicated that the PCs comprising 50% WGC as the fine aggregate and 50% RCA as the coarse aggregates could achieve satisfactory strength and permeability, which could largely meet the requirement of the standard (JIS A 5371) for permeable pedestrian pavers. The appropriate blending of the selected size of WGC (2.36–5 mm) and RCA (5–10 mm) to produce a desirable pore structure in the PCs were responsible for the good performance. In addition, the low thermal conductivity of the produced PCs provided an opportunity to use the PC as partition block materials for saving energy consumption of buildings. Graphical abstract: Image 100 Highlights: A novel sustainable pervious concrete containing waste materials as aggregates is developed. Combined use of waste glass and recycled concrete aggregates in pervious concrete is feasible. The sustainable pervious concrete has satisfactory strength and superior water permeability. The proposed pervious concrete can satisfy the specification for permeable concrete blocks.